Involvement of Platelets in Cancers - Mege, Diane; Aubert, Mathilde; Lacroix, Romaric; Dignat-George, Françoise; Panicot-Dubois, Laurence; Dubois, Christophe (Seminars in Thrombosis and Hemostasis, 2019)
Cancer-related venous thromboembolism (VTE) is frequent and constitutes the second leading cause of death in patients with cancer. High platelet count is one of independent predictive factors of cancer-associated VTE. Besides the implication of platelets in cancer-associated VTE, recent clinical and experimental evidences support that platelets play several roles in the progression of malignancies and inversely, cancer can also influence platelet count and activity. The objective of this report is to review the current literature regarding the role of platelets in cancer through experimental results and population-based studies. Platelets are implicated in cancer progression and metastasis through proangiogenic factors (growth factors and signaling pathways), antiangiogenic factors (angiostatin, endostatin, thrombospondin-1), and matrix metalloproteinases. In addition, platelets are involved in cancer-associated thrombosis and thus tumor cell-induced platelet activation, through anionic phospholipids on their surface, released soluble factors, such as P-selectin, CD40 ligand, platelet factor 4, thrombospondin-1 or beta-thromboglobulin, tumor cell procoagulant proteins (tissue factor, urokinase-type plasminogen activator, plasminogen activator inhibitor type 1), and microparticles. Due to these different mechanisms, platelets may represent a potential therapeutic target. The main current treatments against platelets are: (1) acetylsalicylic acid (aspirin) and nonsteroidal anti-inflammatory drugs, nonselective cyclo-oxygenase (COX)-1 and COX-2 inhibitors, which are associated with decreased cancer incidence and better overall survival and (2) irreversible inhibitor of P2Y12 subtype which decreases cancer incidence. Platelets are key players in tumor growth, metastasis, and cancer-associated thrombosis. This multifaceted role identifies them as a relevant therapeutic target for prevention of cancer occurrence and treatment of cancer.
Keywords: cancer; platelet; thrombosis; aspirin; microparticles